EXPLORING THE SOUL OF ALGORITHMS: A DEEP DIVE INTO THE RISE OF VIRTUAL IN-FLUENCERS IN INDONESIA - Betty Tresnawaty; Muhammad Rif’at Al-Razi; Maylanny Christin (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The emergence of digital technologies initiated never-before-seen changes in the field of marketing, such as the introduction of virtual influencers. Cutting-edge computer animation techniques produce these personalities and are carefully crafted to interact with and sway the opinions of people online. This study intends to analyze the emerging virtual influencer phenomenon that is gradually unfolding in Indonesia’s digital economy, giving particular attention to its evolution, effects, and specific strategies employed in contemporary marketing communication. The purpose is to chart the evolution of virtual influencers in Indonesia and assess their effectiveness as novel digital marketing tools. The approach taken in this study is qualitative descriptive to capture the virtual influencer phenomenon holistically in the context of Indonesia's digital landscape. The results of this study are expected to provide insights and recommendations for digital marketing actors, companies, practitioners, and researchers in designing effective marketing campaigns by utilizing virtual influencers. Computer-generated influencers, also referred to as virtual influencers, have heavy followings which are substantial in number. They are expanding the phenomenon of influencer marketing. These characters are very proficient in endorsing various products and services on different digital platforms, making them valuable marketing assets.